Slaughter value and meat quality of suckler calves: A review. (December 2017) - Domaradzki, Piotr; Stanek, Piotr; Litwińczuk, Zygmunt; Skałecki, Piotr; Florek, Mariusz
Abstract: Veal is widely prized by consumers for its excellent nutritional value. Calf meat is generally obtained from young (immature) bovine animals up to 8 months of age, or in some cases from older animals, but no older than 12 months. Classification of calf carcasses and specification of cuts are quite well regulated in the European market, in contrast with feeding systems and meat characteristics. There are several calf production systems, but in terms of consumer health the most beneficial meat is obtained from animals reared on pasture with natural suckling. In view of the above, this review is limited in scope to Member States of the European Union and focuses on the main factors influencing the carcass quality, proximate composition, intrinsic properties, cholesterol content, fatty acid composition and mineral composition of veal from calves reared on pasture with their mothers.